Delphi: A Democratic and Cost-Effective Method of Consensus Generation in Transplantation - Afrouzian, Marjan; Kozakowski, Nicolas; Liapis, Helen; Broecker, Verena; Truong, Luan; Avila-Casado, Carmen; Regele, Heinz; Seshan, Surya; Ambruzs, Josephine M; Farris, Alton Brad; Buob, David; Chander, Praveen N; et al. (Transplant international, 2023)
The Thrombotic Microangiopathy Banff Working Group (TMA-BWG) was formed in 2015 to survey current practices and develop minimum diagnostic criteria (MDC) for renal transplant TMA (Tx-TMA). To generate consensus among pathologists and nephrologists, the TMA BWG designed a 3-Phase study. Phase I of the study is presented here. Using the Delphi methodology, 23 panelists with >3 years of diagnostic experience with Tx-TMA pathology listed their MDC suggesting light, immunofluorescence, and electron microscopy lesions, clinical and laboratory information, and differential diagnoses. Nine rounds (R) of consensus resulted in MDC validated during two Rs using online evaluation of whole slide digital images of 37 biopsies (28 TMA, 9 non-TMA). Starting with 338 criteria the process resulted in 24 criteria and 8 differential diagnoses including 18 pathologic, 2 clinical, and 4 laboratory criteria. Results show that 3/4 of the panelists agreed on the diagnosis of 3/4 of cases. The process also allowed definition refinement for 4 light and 4 electron microscopy lesions. For the first time in Banff classification, the Delphi methodology was used to generate consensus. The study shows that Delphi is a democratic and cost-effective method allowing rapid consensus generation among numerous physicians dealing with large number of criteria in transplantation.
Keywords: transplantace ledvin; Thrombotic Microangiopathies; Consensus; lidé; Kidney Transplantation; analýza nákladů a výnosů; trombotické mikroangiopatie; Biopsy; konsensus; Cost-Benefit Analysis; biopsie; Humans